A Mobile Health Care Social Networks In Cloud Computing Based On Secure Identity Based Data Sharing and Profile Matching - Apoorva, A; Amoolya, K; Anil, K; Guruprasad, M.; HN, Vinodh (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing and social networks are providing real time data sharing by changing the way of healthcare in a cost-effective manner. However, data security issue is one of the main obstacles of mobile healthcare social networks (MHSN), since health information is considered to be highly sensitive and securable. In this paper, we introduce a mobile health care social networks in cloud computing based on profile matching and data sharing. The patients can outsource their encrypted health records to cloud storage with identity-based broadcast encryption (IBBE) technique, and share them with a group of doctors in a secure and efficient manner with domains and sub domains